An Analysis of the Kinematical Characteristics of an Eccentric Curve-Face Gear Pair with Compound Motion - Chunjiang He; Jinxu Zhang; Chao Lin (Machines, 2024)
An atypical face gear pair with complex transmission motion can be used in intermittent reciprocating mechanisms with more precise transmission and a much higher capacity than conventional mechanisms, such as cams and linkages. In this study, we derive a mathematical equation for the complex tooth surface of this gear pair. We indicate the change in root cutting, top sharpening and the effective width of the tooth surface with different parameters. Additionally, we derive the governing equation for the kinematical characteristics of this eccentric curve-face gear pair with a rigid–flexible coupling system, revealing the continuous intermittent contact principle of this gear type with different parameters. Boundary conditions for the gear pair are proposed, demonstrating that the vibration of the gear pair is more obvious, even at a low velocity. In addition, the critical velocity, which mostly ranges from 300 rpm to 400 rpm, is affected by the stiffness of the frames and the parameters of the tooth surfaces. The interval space and interval time of the intermittent contact system are <semantics>Δd≤0.3 mm</semantics> and <semantics>Δt≤5.6×10−4 s</semantics>, with visible surface sliding on the contact area. It is shown that the contact points are firstly concentrated at the outer part of the tooth surface and that the meshing will break off at the first tooth with the minimum inner radius <semantics>RGi−min</semantics>. These theoretical results, which have been verified experimentally, provide theoretical support for further analysis and the better application of this unconventional gear pair.